Prevalence and Prognostic Significance of Hyponatremia in Patients With Lung Cancer: Systematic Review and Meta-Analysis - Bartalis, Eszter; Gergics, Marin; Tinusz, Benedek; Földi, Mária; Kiss, Szabolcs; Németh, Dávid; Solymár, Margit; Szakács, Zsolt; Hegyi, Péter; Mezösi, Emese; Bajnok, László (Frontiers in Medicine, 2021)
Background The prevalence of hyponatremia is highly variable among lung cancer patients. However, its prevalence and prognostic significance in subgroups of lung cancer patients have not yet been evaluated in a meta-analysis. Methods We have registered our meta-analysis and review protocol to the PROSPERO International Prospective Register of Systematic Reviews, with the following registration number: CRD42020167013. A systematic search was done in the following sources: MEDLINE, Embase, CENTRAL, Web of Science, ClinicalTrials.gov, a WHO Global Health Library. Results We identified a total of 8962 potentially eligible studies and we included 31 articles in our evaluation. The prevalence of hyponatremia in lung cancer patients varied between 3% and 94.8% with an average of 25% without any significant differences between the following subgroups: histotype, gender, age, ECOG state, and the extent of disease. The overall survival (OS) was significantly lower in hyponatremic compared to normonatremic patients at 10 months (RR 0.59, [95% CI 0.47-0.74], p<0.001) and at 20 months (RR 0.44, [95% CI 0.33-0.59], p<0.001), with worse survival rates in NSCLC (RR 0.27, [95% CI 0.12-0.44], p<0.001) than in SCLC (RR 0.42, [95% CI 0.27-0.57], p<0,001). If hyponatremia was corrected, OS at 10 months was significantly higher than in the uncorrected hyponatremia group (RR 1.83, [95% CI 1.37-2.44], p<0,001) but at 20 months no statistically significant difference could be found between these subgroups (RR 2.65, [95% CI 0.94-7.50], p=0.067). Conclusions Lung cancer patients diagnosed with hyponatremia, especially patients with NSCLC, seems to have significantly lower survival rates than normonatremic patients. If hyponatremia remains uncorrected, the mortality rates might be even higher.